Herbert McCabe's Realism - Dunch, Matthew Ian (2022)
This paper defends Herbert McCabe OP against anti-realist charges, particularly Francesca Murphy's extended criticisms of McCabe as a ‘Story Thomist’. McCabe stands accused of reading Thomas Aquinas, in part through Wittgenstein, such that concern for method and language displaces concern for God. Rather, McCabe's story is one of God raising up human beings so that their language and activities develop as they grow in divine life. Beginning with his account of religious obedience, I argue that McCabe is a realist sensitive to the journey of finite creatures towards the mystery of God. Developing in divine life is not primarily informational, but is an entering into the mystery of God so as to share in God's own self-knowledge, a knowledge that humans cannot claim to possess on their own terms. McCabe's Wittgensteinian-inflected Thomism embraces the real gift of divine self-knowledge and the ongoing development of human language and activities in receiving this gift.
Keywords: Obedience; Wittgenstein; Realism; Herbert McCabe; Grammatical Thomism